Evaluation of Vege-Grout Treated Slope by Electrical Resistivity - Baharuddin, INZ; Taha, Hairin; Omar, RC; Roslan, R.; Buslima, FS; Rizal, K (International Journal of Engineering and Technology, 2018)
Soil stabilization using bio-grouting method based on microbial induced calcium carbonate precipitation (MICP) technology has been developed recently to improve the engineering properties of the soil. This new technology could provide an alternative to traditional methods of soil stabilization using soil-cement and chemical grouting. Vegetable waste is a good source for the growth of various kinds of microorganisms which is suitable to be applied as bio-grouting material. The bio-grout extract known as vege-grout was able to induce bio-cementation and bio-clogging process. In this study, vege-grout from vegetable waste was injected into the soil to strengthen the slope and improve the mechanical properties of the affected area. The changes in the subsurface soil after treatment with vege-grout were evaluated by electrical resistivity measurement. Resistivity test showed the resistance in the soil has increased after the grouting using vege-grout.Â Results indicated that the underneath soils have transformed from medium dense sand to dense sand. The water containment in the subsurface appeared to shift deeper into the ground. SEM analysis showed evidence of bio-clogging process as a result of microbial activities in the soil. This analysis showed that the vege-grout from vegetable waste has successfully strengthened and stabilized the slope from soil erosion.